Intramolecular versus intermolecular electronic interactions between [5,6]-open and [6,6]-closed C60 adducts with exTTF - Takano, Yuta; Schubert, Christina; Mizorogi, Naomi; Feng, Lai; Iwano, Azusa; Katayama, Mikimasa; Angeles Herranz, M.; Guldi, Dirk Michael; Martin, Nazario; Nagase, Shigeru; Akasaka, Takeshi (Chemical Science, 2013)
Intramolecular and intermolecular electronic interactions are important concepts for fabricating fullerene-based nanostructures such as bulk heterojunction (BHJ) solar cells and supramolecular assemblies. To ascertain differences of the molecular interactions depending on the electronic characteristics of the fullerene adducts, we have synthesized and investigated the [5,6]-open and [6,6]-closed adducts of C, which are covalently linked to π-extended tetrathiafulvalene (exTTF) by a flexible σ-bond chain. The two adducts were synthesized by means of cycloaddition reactions and were characterized using spectroscopic methods such as MALDI-TOF mass spectrometry and NMR spectroscopy. Electronic properties of the [5,6]-open and [6,6]-closed adducts were investigated in the ground and excited states using steady-state absorption spectroscopy, cyclic and differential pulse voltammetry (CV and DPV), fluorescence spectroscopy, and femtosecond time-resolved absorption spectroscopy. DFT calculations of the two adducts predict that the flexible bridge between C and exTTF enables a closer proximity than the interlayer distance of graphite (3.35 Å), which dictates considerable π-π interactions. In comparing the [5,6]- and [6,6]-adducts, it is noteworthy to mention that the [6,6]-adduct revealed longer lifetimes of the photochemically formed radical ion pair states than that of the [5,6]-adduct, which is in contrast to results of recent investigations related to the photodynamics of [5,6]- and [6,6]-adducts of C. Titration experiments using references, namely [5,6]- and [6,6]-PCBM, inferred that the [6,6]-adduct gives rise to stronger electronic interactions with exTTF than the [5,6]-adduct. Comprehensive understanding of the different molecular properties, which the [5,6]- and [6,6]-adducts exhibit, provides valuable information regarding the morphology and/or the electronic properties of C-based nanocomposites, such as C-based BHJ solar cells or supramolecular assemblies. © 2013 The Royal Society of Chemistry.